Coproducing tobacco control knowledge: Using virtual platforms to strengthen implementation in India - Pragati B Hebbar; Vivek Dsouza; Tshering Bhutia; Prashanth Nuggehalli Srinivas (Wolters Kluwer Medknow Publications, 2022)
Tobacco control is complex and multidimensional. In India, 266.8 million adults use tobacco in some form, with local contextual factors shaping its consumption, production, and trade. Actors have a stake in tobacco represent different sectors; with varying priorities, responding to different ideas, and exerting varying levels of influence often make it difficult to work collaboratively on tobacco control-related issues. Through online networking platforms such as webinars, we emphasize how coproduction of tobacco control knowledge enables participation, prioritizes multisectoral strategies, and enhances tobacco control leadership among policymakers and implementers in their settings. Coproduction of knowledge between and across stakeholders with a focus on "how to" implement tobacco control policies can leverage in negotiating and supplementing the policy implementation process.